Fluorescent Probes Based on Rhodamine Hydrazides and Hydroxamates. Issue 1 (17th November 2015) - Moon, Heejeong; Park, Jinyoung; Tae, Jinsung
Abstract: Rhodamine hydrazides and hydroxamates derived from hydrazines and hydroxylamines have been applied as fluorescent chemosensors. Reaction‐based irreversible probes based on the specific chemical reactions of reactive target species have been developed and applied in bio‐imaging studies. The strong chelation frames provided by the rhodamine hydrazides and hydroxamates have been utilized for the monitoring of metal ions, amino acids, and reactive acid derivatives. This Personal Account focuses on our perspective of developing fluorescent probes based on rhodamine hydrazides and hydroxamates. Abstract : Rhodamine hydrazides and hydroxamates have been developed as selective fluorescent probes utilizing either reaction‐ or chelation‐based ring opening of the rhodamine spirolactam. The extra heteroatom (N for hydrazide and O for hydroxamate) serves as a versatile tool for the introduction of multiple binding units and target‐specific reaction sites.